1993
DOI: 10.1111/j.1476-5381.1993.tb13773.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediation by B1 and B2 receptors of vasodepressor responses to intravenously administered kinins in anaesthetized dogs

Abstract: 1 Vasodepressor responses to intravenous (i.v.) injection of bradykinin (BK) and des-Arg9-BK, a selective B, kinin receptor agonist, were characterized following i.v. pretreatment with selective B, ([Leu8]-des-Arg9-BK) and B2 (Hoe 140) kinin receptor antagonists in anaesthetized dogs. 2 Des-Arg9-BK (0.05-3.3 nmol kg-') produced dose-dependent decreases in mean arterial blood pressure with a ED_0 0.4 nmol kg-'. The vasodepressor effects evoked by des-Arg9-BK (0.6 nmol kg-') and BK (0.2 nmol kg-') were greater a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 16 publications
2
36
0
2
Order By: Relevance
“…25 In addition, residual agonist effects of icatibant have been reported in the rat. 26 Therefore, caution is appropriate when the hypertensive effect induced by icatibant is attributed to selective blockade of the B 2 receptor. However, consistent with the evidence provided by the use of the antagonist is the report that Brown Norway Katholiek rats, a strain congenitally deficient in kininogen in plasma and devoid of kinin release in urine, exhibit a more rapid BP increase during DOC-salt treatment than normal Brown Norway Kitasato rats.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, residual agonist effects of icatibant have been reported in the rat. 26 Therefore, caution is appropriate when the hypertensive effect induced by icatibant is attributed to selective blockade of the B 2 receptor. However, consistent with the evidence provided by the use of the antagonist is the report that Brown Norway Katholiek rats, a strain congenitally deficient in kininogen in plasma and devoid of kinin release in urine, exhibit a more rapid BP increase during DOC-salt treatment than normal Brown Norway Kitasato rats.…”
Section: Discussionmentioning
confidence: 99%
“…7 B 1 receptors are constitutively and functionally expressed in the arterial vessels and glomerulus of rats, 8,9 in the pulmonary vascular bed of cats, 10 and in the arterial vessels of pigs 11 and dogs. [12][13][14] In humans, a recent in vitro study using immunolabeling techniques revealed the presence of B 1 receptors in vascular endothelial and smooth muscle cells of large elastic arteries, muscular arteries (such as coronary arteries), and muscular arterioles. 15 The functional role of constitutive B 1 receptors in the arterial vessels of dogs is well documented.…”
mentioning
confidence: 99%
“…15 The functional role of constitutive B 1 receptors in the arterial vessels of dogs is well documented. [12][13][14] The stimulation of these receptors produces a vasorelaxation and a reduction in blood pressure. [12][13][14] However, their physiological implications in the coronary circulation remain to be determined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…B1R-mediated hypotensive responses have been demonstrated and characterized in the rabbit (24), rat (25), pig (29) and dog (30). Although those studies were carried out under inflammatory conditions, their respective authors suggested that early decrease in mean arterial pressure is due to an acute decrease in peripheral vascular resis-…”
Section: Functional Roles Of B1r In Shr-spmentioning
confidence: 99%